The test of compulsion in mental health law: capacity, therapeutic benefit, and dangerousness as criteria for compulsion - Bartlett, Peter (Oxford University Press, 2003)
This paper considers three possible justifications for psychiatric compulsion - dangerousness, capacity and therapeutic benefit.